Primary Pupil´s Perceptions of their participation on a Performative Music project Crianças ao Palco - Milhano, Sandrina (2021)
The present study is based on a socio-cultural perspective of music education, in which the contexts of musical participation and learning that are provided to the children can assume an important role in the formulation of their perceptions, in the opinions and attitudes that they build and rebuild on music and on themselves. It focuses on understanding the musical and socio-cultural contribution of the project named Crianças ao Palco, a music project available since 2010 in the Leiria region, in Portugal, for primary schools. This project aims to develop and improve pupil’s artistic, cognitive and social skills through a voice selection process in order to participate in a final musical performance [1]. As suggested by Milhano [2] in a study developed with pupils from the same region, musical participation in the different contexts of primary music education seems to be an activity participated in only by a minority. They include children participation in musical activities both at school as a compulsory subject, and outside school as an elective subject in formal and informal dimensions. Suggestion was made upon the importance of nurturing pupil’s opportunities to actively take part in each one of the potential and desirable contexts of music education, especially music at primary school [3]. The present study aimed to understand the meanings assigned by pupils to the experience of participating in the project, characterizing their contexts of musical participation, before and after the experience. Results were drown on a questionnaire survey, made available online to pupils participating in the final shows between the years 2010 and 2017, and on structured interviews made with parents and primary school teachers. Results suggests that, for many pupils, the project allowed their first contacts with professional musicians, and later, encouraged their search for opportunities for a greater musical involvement as the pursuit of further studies in music education. The positive experiences and musical, social and emotional memories gathered by pupils generated new musical perspectives in their lives and ways of participation and involvement